2016
DOI: 10.2174/1745017901612010075
|View full text |Cite
|
Sign up to set email alerts
|

State of Acute Agitation at Psychiatric Emergencies in Europe: The STAGE Study

Abstract: Background:Agitation is an array of syndromes and types of behaviors that are common in patients with psychiatric disorders. In Europe, the estimation of prevalence of agitation has been difficult due to the lack of standard studies or systematic data collection done on this syndrome.Objective:An observational, cross-sectional, multicenter study aimed to assess the prevalence of agitation episodes in psychiatric emergencies in different European countries.Method:For 1 week, all episodes of acute agitation that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 34 publications
2
33
1
3
Order By: Relevance
“…Examining these and other factors that contribute to the use of seclusion and restraints are important so that changes in policies and practices could be made to further reduce or minimize their use (Allen et al, ; Knox & Holloman, ; Lofchy, Boyles, & Delwo, ; Richmond et al, ). At a prevalence of 32.4%, the use of seclusion in our hospital is higher than the pooled prevalence of 29% reported for children and adolescents in psychiatric settings (De Hert, Dirix, Demunter, & Correll, ), and also appears high compared to the published estimate of the prevalence of conditions (Allen et al, ; San et al, ) that may require their use. In the literature, restraints and seclusion continue to be two of the most frequently reported interventions used to manage challenging behaviour (Cowman, Björkdahl, Clarke, Gethin, & Maguire, ), despite lack of strong evidence of effectiveness (Nelstrop et al, ) and potential for long‐term negative outcomes (McLaughlin, Giacco, & Priebe, ).…”
Section: Discussioncontrasting
confidence: 63%
“…Examining these and other factors that contribute to the use of seclusion and restraints are important so that changes in policies and practices could be made to further reduce or minimize their use (Allen et al, ; Knox & Holloman, ; Lofchy, Boyles, & Delwo, ; Richmond et al, ). At a prevalence of 32.4%, the use of seclusion in our hospital is higher than the pooled prevalence of 29% reported for children and adolescents in psychiatric settings (De Hert, Dirix, Demunter, & Correll, ), and also appears high compared to the published estimate of the prevalence of conditions (Allen et al, ; San et al, ) that may require their use. In the literature, restraints and seclusion continue to be two of the most frequently reported interventions used to manage challenging behaviour (Cowman, Björkdahl, Clarke, Gethin, & Maguire, ), despite lack of strong evidence of effectiveness (Nelstrop et al, ) and potential for long‐term negative outcomes (McLaughlin, Giacco, & Priebe, ).…”
Section: Discussioncontrasting
confidence: 63%
“…There is limited epidemiologic evidence on the prevalence of agitation in mental health settings. Estimates range between a high of 47.5% among newly hospitalised adults with schizophrenia in China [8] to a low of 4.6% among psychiatric emergency presentations in Europe [9]. This variation is due in part to the ongoing debate over a standardised de nition of agitation and the use of appropriate measurement scales to aid the assessment of agitation in the clinical setting [10].…”
Section: Introductionmentioning
confidence: 99%
“…Although agitation states from mild to severe and their characterization have been previously described, there has been a failure to reach a consensus on the definition of agitation [ 6 , 7 ] which has been recognised as one factor underlying the lack of epidemiological data in this area [ 8 ]. Previous studies that have reported on the prevalence of agitation focus on emergency hospital or clinic attendance; a European study found that 4.6% of psychiatric emergencies were attributed to acute agitation, of which half of the patients had a diagnosis of schizophrenia and a quarter had a diagnosis of bipolar disorder [ 9 ]. Conversely, a US study found that 52% of psychiatric emergencies included agitation to some degree; [ 10 ] the discrepancy between the two studies is likely a result of differential definitions and an under-diagnosis of mild or moderate episodes [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies that have reported on the prevalence of agitation focus on emergency hospital or clinic attendance; a European study found that 4.6% of psychiatric emergencies were attributed to acute agitation, of which half of the patients had a diagnosis of schizophrenia and a quarter had a diagnosis of bipolar disorder [ 9 ]. Conversely, a US study found that 52% of psychiatric emergencies included agitation to some degree; [ 10 ] the discrepancy between the two studies is likely a result of differential definitions and an under-diagnosis of mild or moderate episodes [ 9 ]. The data from these studies indicate that agitation is observed in psychiatric emergencies, but do not provide insight into the day-to-day burden of agitation in the community.…”
Section: Introductionmentioning
confidence: 99%